Combined linkage and association mapping identifies a major QTL (qRtsc8-1), conferring tar spot complex resistance in maize - Mahuku, George S.; Chen, J.; Shrestha, R.; Narro, L.A.; Guerrero, K.V.; Arcos, A.L.; Xu, Y. (Springer, 2016)
Tar spot complex (TSC) is a highly destructive disease of maize found in some countries in America. Identification of TSC resistant germplasm and elucidating the genetic mechanism of resistance is crucial for the use of host resistance to manage this disease. We evaluated 890 elite maize inbred lines in multiple environments and used genome wide association analysis (GWAS) with genotypic data from Illumina MaizeSNP50 BeadChip containing 56 K SNPs to dissect the genetics of TSC resistance. GWAS results were validated through linkage analysis in three bi-parental populations derived from different resistant and susceptible parents. Through GWAS, three TSC resistance loci were identified on chromosome 2, 7 and 8 (−log10 (p) > 5.99). A major quantitative resistance locus (QTL) designated qRtsc8-1, was detected on maize chromosome bin 8.03. qRtsc8-1, was confirmed in three independent bi-parental populations and it accounted for 18–43 % of the observed phenotypic variation for TSC. A rare haplotype within the qRtsc8-1 region, occurring at a frequency of 3.5 % increased TSC resistance by 14 %. Candidate gene analysis revealed that a leucine-rich repeat receptor-like protein (LRR-RLKs) gene family maybe the candidate gene for qRtsc8-1. Identification and localization of a major locus conditioning TSC resistance provides the foundation for fine mapping qRtsc8-1 and developing functional markers for improving TSC resistance in maize breeding programs. To the best of our knowledge, this is the first report of a major QTL for TSC resistance.